(untitled) (JOURNAL OF UNIVERSITY OF BABYLON for Pure and Applied Sciences, 2021)
Aeromagnetic data of an extensive area covering sheets 243 and 244 (Ilesa-Ado-Ekiti) from the Nigerian Geological Survey Agency (NGSA) were subjected to data enhancement filters and thereafter profiled into eleven (11) lines and interpreted quantitatively using forward modeling method to estimate depths to magnetic dykes and contacts of all lines. The profile depths solution revealed depths to dykes ranged from 209 – 494 m and depths to contact ranges from 35 – 498 m. Also, Euler De-convolution solution of structural index one (1) used to model dykes revealed depths ranging from 177-4389.8 m while Euler De-convolution of structural index 0.5 used to model contacts revealed depths ranging from 162-3262.8 m. Lastly, the Local Wave Number (LWN) result showed that depths to the magnetic contacts ranges from 277.2-4529.7m and which resolved best for deepest seated contact. The results obtained from this work are vital information for recognition of geological features such as contacts and dykes.